Pengaruh Leverage Dan Ukuran Perusahaan Terhadap Rating Sukuk Dengan Profitabilitas Sebagai Variabel Intervening (Studi Empiris Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index) - Zatta Gahassani Hasibuan; Widia Astuty; Eka Nurmala Sari (Jurnal Riset AKuntansi dan Bisnis, 2023)
The purpose of this research is to find out, test and analyze the effect of leverage and company size on profitability. To find out, test and analyze the effect of leverage and company size on sukuk ratings. To find out, test and analyze the effect of profitability on sukuk ratings. To find out, test and analyze Profitability mediates the influence of leverage and company size on sukuk ratings. The type of research used in this research is associative quantitative research. The total number of companies registered on the Jakarta Islamic Index (JII) in 2018-2021 which is the population in this research is 44 companies. Based on the criteria, the companies that can be used as samples in this research are 15 companies. Data analysis in this research is a statistical analysis method using Structural Equation Modeling (SEM) type Partial Least Squares (SEM PLS). Based on research results. The t-statistic value of 4,4141.98 and P-value 0.0000.05 indicate that DER has an effect on the sukuk rating.